2010
DOI: 10.1007/s00330-010-1905-5
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic accuracy of US, CT, MRI and 1H-MRS for the evaluation of hepatic steatosis compared with liver biopsy: a meta-analysis

Abstract: ObjectiveTo meta-analyse the diagnostic accuracy of US, CT, MRI and 1H-MRS for the evaluation of hepatic steatosis.MethodsFrom a comprehensive literature search in MEDLINE, EMBASE, CINAHL and Cochrane (up to November 2009), articles were selected that investigated the diagnostic performance imaging techniques for evaluating hepatic steatosis with histopathology as the reference standard. Cut-off values for the presence of steatosis on liver biopsy were subdivided into four groups: (1) >0, >2 and >5% steatosis;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
396
2
24

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 466 publications
(426 citation statements)
references
References 74 publications
4
396
2
24
Order By: Relevance
“…Furthermore, without liver biopsy, it is impossible to characterize liver histology such as degree of fibrosis and distinguish between nonalcoholic fatty liver and nonalcoholic steatohepatitis because nonalcoholic steatohepatitis can progress to cirrhosis, liver failure, and liver cancer and increase hepatic and extrahepatic morbidity and mortality (Chalasani et al 2012). However, a meta-analysis from 46 articles comparing various imaging modalities to liver biopsy for diagnosis of NAFLD concluded that mean sensitivity estimates for US and CT were 73.3-90.5 and 46.1-72.0%, respectively, and mean specificity range were 69.6-85.2 and 88.1-94.6% respectively (Bohte et al 2011). Specificity, sensitivity, positive predictive value, and negative predictive value of unenhanced CT liver attenuation alone with threshold of 48 HU for diagnosis of NAFLD used in this study were 100, 53.8, 100, and 93.9% respectively; these values are highly specific for diagnosing hepatic steatosis (Pickhardt et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, without liver biopsy, it is impossible to characterize liver histology such as degree of fibrosis and distinguish between nonalcoholic fatty liver and nonalcoholic steatohepatitis because nonalcoholic steatohepatitis can progress to cirrhosis, liver failure, and liver cancer and increase hepatic and extrahepatic morbidity and mortality (Chalasani et al 2012). However, a meta-analysis from 46 articles comparing various imaging modalities to liver biopsy for diagnosis of NAFLD concluded that mean sensitivity estimates for US and CT were 73.3-90.5 and 46.1-72.0%, respectively, and mean specificity range were 69.6-85.2 and 88.1-94.6% respectively (Bohte et al 2011). Specificity, sensitivity, positive predictive value, and negative predictive value of unenhanced CT liver attenuation alone with threshold of 48 HU for diagnosis of NAFLD used in this study were 100, 53.8, 100, and 93.9% respectively; these values are highly specific for diagnosing hepatic steatosis (Pickhardt et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…As such, the macroscopic identification of FLD using non-invasive imaging techniques has been advocated for the diagnosis of nonalcoholic FLD (7). At present, various radiological methods can detect the presence of fat in the liver, including abdominal ultrasound, CT, and MRI (6). Ultrasonography may reveal hyperechoic liver parenchymal echotextures, although this is a non-specific finding (20).…”
Section: Discussionmentioning
confidence: 99%
“…Serum alanine aminotransferase, however, correlates somewhat with infl ammation, but not with liver steatosis. US, on the other hand, has an adequate diagnostic accuracy for detecting moderate or severe hepatic steatosis in the adult population in general, with pooled sensitivities ranging from 85.7% to 91.1% and pooled specifi cities ranging from 85.2% to 91.9% in a recently published meta-analysis ( 6 ). All data were obtained from studies that compared US with histopathologic evaluation.…”
Section: Study Design and Patientsmentioning
confidence: 99%